One for all and all for one: Increasing the adaptive capacity of households and communities through a public work programme - Scognamillo, Antonio; Mastrorillo, Marina; Ignaciuk, Adriana (Elsevier, 2024)
This article uncovers the mechanisms shaping the impact of the public work component of Ethiopia’s Productive Safety Net Programme (PSNP) on beneficiaries and communities’ food security and vulnerability to various shocks. Using three waves of a national representative household survey, this study provides quantitative evidence on the pathways through which the social protection intervention affects direct beneficiaries and their community peers. The empirical findings show that the PSNP beneficiaries are less likely to be food insecure and to experience harvest losses in the aftermath of droughts. Notably, the beneficial effects of the programme partially spill over to the direct participants’ community peers. This is likely to be due the nature of the public works implemented through the programme, such as the integrated community-based watershed development, including soil and water conservation measures and rangeland management in pastoral areas. Additionally, no significant impacts have been found when households self-report stresses unrelated to droughts. Our findings are expected to inform the debate on the effectiveness of the PSNP and other adaptive social protection programmes. From a policy perspective, they suggest the explicit integration of environmental and climate considerations into the design of social protection interventions targeting poor agricultural households highly vulnerable and exposed to weather shocks.